1976
DOI: 10.1007/bf02396641
|View full text |Cite
|
Sign up to set email alerts
|

On the spheroidization of rod-shaped particles of finite length

Abstract: The governing equation for the capillarity-induced shape changes of a surface of revolution by surface diffusion, ~n B~ (v~K) ~t -y ~s ~s where ~n/~t is the normal velocity of the surface, y is measured normal to the axis of revolution, s is arc length, K is the total surface curvature and B is a kinetic parameter which is constant for a given temperature and material, is presented. A numerical solution to this equation is used to analyse finite cylinders with hemispherical ends. A critical length-to-diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(61 citation statements)
references
References 11 publications
2
59
0
Order By: Relevance
“…(2) Expansion and contraction happened in radial direction, which finally caused the break-up of slender MnS. Numerical simulation of shape evolution for a rod has been done by Nichol et al 10,11) It's found that for the rod (L/D=7.19), the length recedes toward each other. Simultaneously, Bulges near the two ends and necking in the middle occur, which finally form two egg-shaped particles.…”
Section: In-situ Observationmentioning
confidence: 99%
“…(2) Expansion and contraction happened in radial direction, which finally caused the break-up of slender MnS. Numerical simulation of shape evolution for a rod has been done by Nichol et al 10,11) It's found that for the rod (L/D=7.19), the length recedes toward each other. Simultaneously, Bulges near the two ends and necking in the middle occur, which finally form two egg-shaped particles.…”
Section: In-situ Observationmentioning
confidence: 99%
“…It is caused by self necking phenomena from the large curvature ends. The average spacing among the broken-up voids, termed the critical wavelength l c , is given theoretically by l c ¼2 3/2 pR c $8.9R c , where R c is the initial pore radius [6,9,15]. The critical wavelength corresponds to a perturbation in the pore morphology, as determined by the mechanics of capillary motion.…”
Section: Resultsmentioning
confidence: 99%
“…From a micromechanical perspective, healing and sealing of cracks involves a sequence of modifications first of planar then of cylindrical void surfaces, and it has been suggested that the ovulation of cylindrical pores due to the RayleighTaylor instability (Nichols, 1976) is rate-controlling in this complex process (e.g., Smith and Evans, 1984). The ovulation in turn is controlled by the same kinetic parameters as hydrothermal grooving.…”
Section: Discussionmentioning
confidence: 99%